Stabilization of the Chest Wall: Autologous and Alloplastic Reconstructions - Mahabir, Raman Chaos (Thieme Medical Publishers, 2011)
The goals of chest wall stabilization include maintenance of a rigid airtight cavity, protection of the thoracic and abdominal contents, optimization of respiration, and, whenever possible, an aesthetic reconstruction. Evidence suggests that bony fixation results in reduced ventilator dependence, a shorter overall hospital stay, and improved upper extremity function. We prefer to accomplish this with autologous tissue alone (such as the pectoralis major, latissimus dorsi, or rectus abdominus muscle flaps) for small to moderate defects. En bloc resection of defects larger than 5 cm or containing four or more ribs will likely benefit from chest wall stabilization. For patients previously treated with radiation, even larger defects may be tolerated owing to fibrosis. For these larger defects, methyl methacrylate composite meshes are used and covered with vascularized tissue. Contaminated wounds are generally reconstructed with bioprosthetic mesh rather than synthetic mesh. Using these principles, the reconstructive plastic surgeon can devise a comprehensive and safe plan to repair tremendous defects of the chest wall.